VALUATION UNDER RAINFED CONDITIONS OF DURUM WHEAT VARIETIES GENERATED FOR IRRIGATION - Villaseñor Mir, Héctor Eduardo; Limón Ortega, Agustín; Rodríguez García, María Florencia; Martínez Cruz, Eliel; Santa Rosa, René Hortelano; Mariscal Amaro, Luis Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to know the possibilities of producing crystalline wheat with good yields and quality in rainfed areas of High Valleys of Mexico, an experiment was established in four different production environments, where wheat varieties Topacio C98, Júpare C2001 and Gema C2004 were tested and compared with bread wheat varieties Rebeca F2000 and Tlaxcala F2000, which were developed for rainfed conditions; genotypes were evaluated with and without fungicide application. The results indicate that the bread wheat varieties overcame for its agronomic and yield characteristics to the durum wheat in all the testing sites, obtaining higher yields up to 20% (1 200 kg ha-1). Bread wheat had higher yields and was the best option in evaluated favorable production environments and the best alternative in critical environments. Due to its agronomic performance and yield, Júpare C2001 was the durum wheat with better response and adaptation in the tested environments. The industrial quality of durum wheat in any condition, allowed obtaining suitable semolina for the manufacture of good quality products, but its production under rainfed conditions could be an alternative for using it as a flour mixtures improver.
Keywords: bread wheat; durum wheat; industrial quality; irrigation and rainfed